KOH-Activated Dragon Fruit Peels for Cd2+ Ions Adsorption from Water: english - Lestari, Puji; Pryadi, M. Ichtiar; Siswoyo, Eko (Asian Journal of Innovation and Entrepreneurship, 2024)
This study investigates the potential of KOH-activated dragon fruit peels as an adsorbent for the removal of Cd2+ ions from solution. The adsorption performance of the activated dragon fruit peels was evaluated through batch adsorption experiments, where various parameters including adsorbent dosage, initial Cd2+ concentration, contact time, and solution pH were examined. The optimum condition for the adsorption process was pH 5, stirring time 120 min, adsorbent dosage of 20 mg (in 25 mL solution).  The findings highlight the potential of utilizing agricultural waste materials, such as dragon fruit peel, as an effective and sustainable adsorbent for the removal of heavy metal ions from water sources, contributing to environmental remediation efforts.